2015
DOI: 10.4238/2015.november.18.14
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a benzoic acid/salicylic acid carboxyl methyltransferase gene involved in floral scent production from lily (Lilium ‘Yelloween’)

Abstract: ABSTRACT. In lily flowers, the volatile ester methyl benzoate is one of the major and abundant floral scent compounds; however, knowledge regarding the biosynthesis of methyl benzoate remains unknown for Lilium. In this study, we isolated a benzoic acid/salicylic acid carboxyl methyltransferase (BSMT) gene, LiBSMT, from petals of Lilium 'Yelloween'. The gene has an open reading frame of 1083 base pairs (bp) and encodes a protein of 41.05 kDa. Sequence alignment and phylogenetic analyses of LiBSMT revealed 40-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Activity with SA and BA has likely been maintained since relatively early in the history of the monocot lineage because the BSMT orthologs we characterized from Musa and Phalaenopsis (Zingiberales and Asparagales, respectively) show activity with both substrates ( fig. 4 ) as does a previously reported one from Lilium (Liliales) ( Wang et al 2015 ). Second, the phylogenetic analysis and characterization of a Carica SAMT sequence ( fig.…”
Section: Resultssupporting
confidence: 82%
“…Activity with SA and BA has likely been maintained since relatively early in the history of the monocot lineage because the BSMT orthologs we characterized from Musa and Phalaenopsis (Zingiberales and Asparagales, respectively) show activity with both substrates ( fig. 4 ) as does a previously reported one from Lilium (Liliales) ( Wang et al 2015 ). Second, the phylogenetic analysis and characterization of a Carica SAMT sequence ( fig.…”
Section: Resultssupporting
confidence: 82%
“…S22a-27a). It has been confirmed that SAMT is a key gene regulating the synthesis of floral aromatic VOCs in various plant species, such as Clarkia amoena, Lilium, Jasminum sambac, and Eriobotrya japonica [36][37][38][39][40][41]. The release of methyl salicylate peaked at the flower-bud stage and remained stable throughout the floral growth and developmental stages, and SAMT expression was downregulated after the petals opened.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PAL was down-regulated in YJB and YJC, it was signi cantly negatively correlated with various benzene-like VOC, and signi cantly positively correlated with non-volatile benzene-like substances. Verdonk et al [45] used DNA microarray analysis and found that the key enzyme PAL for benzene synthesis was found to be transcriptionally induced before the onset of VOC release, and then combining HS-SPME-GC-MS technology and targeted metabolomics method to monitor VOC release in petunia hybrid W115. Finally, Verdonk et al found that PAL regulates the production of petunia aroma VOC.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SAMT was up-regulated in YJD and was signi cantly negatively correlated with benzene VOC. It has been con rmed that SAMT is a key gene regulating the synthesis of oral aroma VOC in various plants such as Clarkia amoena, Lilium, Jasminum sambac, and Eriobotrya japonica [43][44][45][46][47][48]. Dudareva et al [43] found that petals are the main tissue site for the release of methyl salicylate, and the activity of salicylate carboxymethyl transferase was the highest in petal tissues, and peaked in petals during the blooming period a few days after owering decreased, which was strongly positively correlated with the release of methyl salicylate.…”
Section: Discussionmentioning
confidence: 99%